Pengaruh Pendapatan Premi, Beban Klaim Dan Hasil Underwriting Terhadap Pertumbuhan Laba Pada PT Asuransi Sinar Mas - Rahmah Sari Lubis; Fauzi Arif Lubis; Nurul Inayah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
Profit growth is the difference between the profits obtained by the company this year and those obtained in the previous quarter or year, whether there was an increase in profits or even vice versa. This increase in profit growth is something that all companies want to achieve. By increasing profits in a company, profits can also increase the value of the company, because profits are very important for the continuity of company operations. Financial reports are one method for measuring the increase in insurance company profits. The aim of this research is to find out how premium income, claims expenses and underwriting results influence PT Asuransi Sinar Mas's ability to increase profits. This research is quantitative in nature and uses a saturated sampling strategy to collect secondary data from financial reports on the Sinar Mas Insurance website. According to the findings from the analysis that has been carried out, premium income and underwriting results seem to show an influence on each variable on profit growth. Meanwhile, claims expenses showed absolutely no impact on profit growth. From the F test table, profit growth is simultaneously influenced by premium income, claims expenses and underwriting results.